2011
DOI: 10.1371/journal.pone.0023739
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Changes Related to Disease Duration in Patients with Asthma

Abstract: Dyspnea is the impairing, cardinal symptom patients with asthma repeatedly experience over the course of the disease. However, its accurate perception is also crucial for timely initiation of treatment. Reduced perception of dyspnea is associated with negative treatment outcome, but the underlying brain mechanisms of perceived dyspnea in patients with asthma remain poorly understood. We examined whether increasing disease duration in fourteen patients with mild-to-moderate asthma is related to structural brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 54 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…Changes in these brain structures were related to illness duration [34]. The insular cortex is an important multisensory integration area involved in the processing of various unpleasant bodily signals and emotions, while the PAG plays an important role in the up- and downregulation of pain sensations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these brain structures were related to illness duration [34]. The insular cortex is an important multisensory integration area involved in the processing of various unpleasant bodily signals and emotions, while the PAG plays an important role in the up- and downregulation of pain sensations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have demonstrated that brain areas with high relevance to emotion processing such as the insular cortex, anterior cingulate cortex and amygdala play an important role in the processing of dyspnea, presumably for its affective aspects (Evans, 2010; von Leupoldt, Sommer et al, 2008). There is evidence that negative affective quality of dyspnea can habituate in some asthma patients, which is accompanied by insular cortex down-regulation as well as functional and structural up-regulation in the brainstem periaqueductal grey (von Leupoldt et al, 2009, von Leupoldt, Brassen, Baumann, Klose & Büchel, 2011). First attempts have also been documented linking neural processing of asthma-relevant stimuli with airway and inflammatory responses to allergen challenge (Rosenkranz & Davidson, 2009)…”
Section: Psychosocial Influences On Asthma: Psychobiology and Health mentioning
confidence: 99%
“…The newborns with congenital heart disease (45,46). For other diseases, changes have been found in adult brain for type 2 diabetes (47-50), asthma (51,52), and chronic obstructive pulmonary disease (53)(54)(55). Improvements in diagnostic methods will make it possible to establish changes during early life.…”
Section: The Role Of Hypoxia In the Neurogenesis Stimulationmentioning
confidence: 99%